Influence of Colour Difference over Visibility in Multimedia Projection - Masiokas, S.; Kriuglaitė, M. (Elektronika ir Elektrotechnika, 2010)
Colour luminance contrast between task and background is the most contributory visibility factor in digital projection image, its ef-fect was earlier investigated. Influence of chromatic constituents over visibility is not so significant, but must be also evaluated. Chro-matic contrast and colour difference become deciding when colour luminance contrast between task and background is low or equals to zero. It’s topical in case of ambient light, which discolours image on screen. Fundamental colour difference formulas, their particularity of use in uniform colour spaces are discussed in this paper. Primal computer colours combinations of best visibility for positive and ne-gative image are ascertained.